Significant differences in the use of healthcare resources of native-born and foreign born in Spain - de Andrés Ana; Barrera Valentin; Jiménez-García Rodrigo; Carrasco-Garrido Pilar; de Miguel Ángel (BMC, 2009)
Abstract Background In the last decade, the number of foreign residents in Spain has doubled and it has become one of the countries in the European Union with the highest number of immigrants There is no doubt that the health of the immigrant population has become a relevant subject from the point of view of public healthcare. Our study aimed at describing the potential inequalities in the use of healthcare resources and in the lifestyles of the resident immigrant population of Spain. Methods Cross-sectional, epidemiological study from the Spanish National Health Survey (NHS) in 2006, from the Ministry of Health and Consumer Affairs. We have worked with individualized secondary data, collected in the Spanish National Health Survey carried out in 2006 and 2007 (SNHS-06), from the Ministry of Health and Consumer Affairs. The format of the SNHS-06 has been adapted to the requirements of the European project for the carrying out of health surveys. Results The economic immigrant population resident in Spain, present diseases that are similar to those of the indigenous population. The immigrant population shows significantly lower values in the consumption of alcohol, tobacco and physical activity (OR = 0.76; CI 95%: 0.65-0.89, they nonetheless perceive their health condition as worse than that reported by the autochthonous population (OR = 1.63, CI 95%: 1.34-1.97). The probability of the immigrant population using emergency services in the last 12 months was significantly greater than that of the autochthonous population (OR = 1.31, CI 95%: 1.12-1.54). This situation repeats itself when analyzing hospitalization data, with values of probability of being hospitalized greater among immigrants (OR = 1.39, CI 95%: 1.07-1.81). Conclusion The economic immigrants have better parameters in relation to lifestyles, but they have a poor perception of their health. Despite the fact that immigrant population shows higher percentages of emergency attendance and hospitalization than the indigenous population, with respect to the use of healthcare resources, their usage of healthcare resources such as drugs, influenza vaccinations or visits to the dentist is lower.